Oral administration of chios mastic gum or extracts in mice: Quantification of triterpenic acids by liquid chromatography-tandem mass spectrometry - Lemonakis, N.a b; Magiatis, P.b; Kostomitsopoulos, N.c; Skaltsounis, A.-L.b; Tamvakopoulos, C.a (Planta Medica, 2011)
Chios mastic gum, the resin obtained as an exudate from the trunk and branches of Pistacia lentiscus L var. chia, is used extensively as a constituent of herbal drugs or functional foods. The oral absorption of its major constituents still remains unclear. In the context of identifying the features of mastic gum that are responsible for either therapeutic effects or effects of nutritional value, a methodology based on high-performance liquid chromatography (HPLC) coupled to tandem mass spectrometry (MS/MS) was developed and applied for the quantification of mastic gum triterpenic acids, 24Z-isomasticadienonic acid (IMNA), and 24Z-isomasticadienolic acid (IMLA) in mouse plasma. The specific compounds were selected based on their biological activity and potential against Helicobacter pylori. Concentrations were determined simultaneously in mouse plasma after oral administration of mastic gum or total mastic extract without polymer (TMEWP) in order to evaluate the role of the natural polymer, poly - myrcene, in the absorption process. Following TMEWP administration in mice, circulating IMNA and IMLA plasma levels were significantly higher (approximately 10-fold) in comparison to IMNA and IMLA plasma levels following total mastic gum administration (CMG), suggesting that the polymer plays a critical role in the absorption process. More specifically following TMEWP administration, Cmax plasma values were 3300±859ng/mL for IMNA and 163±58ng/mL for IMLA. In comparison, following CMG administration, Cmax plasma values were 329±57ng/mL for IMNA and 28±8ng/mL for IMLA. The methodological approaches presented in this study, along with the findings, offer valuable information on the availability of bioactive components following ingestion of mastic and facilitate the uses of mastic either as an ingredient of functional foods or as a herbal drug. © Georg Thieme Verlag KG Stuttgart - New York.
Keywords: 24 isomasticadienolic acid; 24 isomasticadienonic acid; Absorption; accuracy; Administration; animal experiment; Animals; article; biological activity; Chios mastic gum; Chromatography; controlled study; drug absorption; drug blood level; drug isolation; Helicobacter pylori; high performance liquid chromatography; Inbred C57BL; limit of quantitation; Liquid; Male; maximum plasma concentration; medicinal plant; Mice; Microbial Sensitivity Tests; moronic acid; mouse; myrcene; nonhuman; oleanonic acid; Oral; Pistacia; Pistacia lentiscus extract; Plant; Plant Extracts; plant medicinal product; Plant Stems; Resins; tandem mass spectrometry; total mastic extract without polymer; triterpene derivative; unclassified drug